The relationship between corporate governance mechanisms and firm performance : the mediating effect of real earnings management - Dakhlallh, Mohammad Mustafa Mohammad
The corporate governance mechanisms are designed for the effective and efficient operation of companies on behalf of the shareholders against the opportunistic behaviours among managers. Financial manipulation among managers in business organizations is caused by a number of financial opportunities. The most frequent issues that come to the forefront relate to corporate failures are financial manipulations activities engaged by unethical managers of the companies. This study aims to investigate the mediating effect of real earnings management on the relationship between corporate governance mechanisms and firm's performance. In this study, financial and non-financial data were collected from 180 companies listed in Amman Stock Exchanges (ASE) from 2009 to 2017. The investigation covered a period f nine years and consisted of 1620 firms years of observation. The balanced panel data approach was used to analyze the direct and indirect effects of the selected variables for further analyses determined by specification methods comprising Fixed Effect regression analyses. The corporate governance mechanisms examined include the board structure (size, independence, and CEO duality), ownership structure (managerial, family, government, and block holders), audit committee (size, independence, and audit committee ownership members). Consequently, the measurement used for real earnings management related to cash flow from operations, while the measurement for the firm's performance referred to market based (Tobin s Q). The finding of the tudy indicates that corporate governance mechanisms have a significant influence on a firm's performance and real earnings management, while managerial ownership and block holders have an insignificant effect on the firm's performance. The results also showed that real earnings management mediates the relationship between corporate governance and firm's performance, while no mediation relationship for managerial ownership and block holders. This study provides relevant financial information to shareholders in the capital market to be utilized by selected companies. The results also show several implications to investors, policymakers, researchers, and regulators, especially concerning better investment decisions in the capital market and enhancing the firm's performance.